2012
DOI: 10.5858/arpa.2011-0319-oa
|View full text |Cite
|
Sign up to set email alerts
|

Potassium but Not Lactate Dehydrogenase Elevation Due To In Vitro Hemolysis Is Higher in Capillary Than in Venous Blood Samples

Abstract: N Context.-Elevated potassium concentrations due to in vitro hemolysis can lead to errors in diagnoses and treatment. Recently, we observed that potassium elevation in capillary samples appeared higher than expected, based on hemolytic index (H-index).Objective.-To investigate the relation between potassium increase and H-index for capillary samples. As a control, the same analysis was performed for lactate dehydrogenase (LDH).Design.-Potassium results of 332 760 venous and 2620 capillary samples were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…29 The elevation of potassium due to hemolysis has been reported to be more important in capillary blood samples compared to venous blood samples, which is of special interest to POCT applications. 32 It was also shown that temperature during transport might lead to misdiagnosis and "pseudo hyperkalemia", or so-called "seasonal pseudohyperkalemia". 33 To alleviate this issue, a study showed that the introduction of centrifuges in UK GP surgeries led to a reduction of these cases, thereby proving the benefits of rapid, point-of-care plasma extraction.…”
Section: Influence Of Hemolysis In Blood Samplesmentioning
confidence: 99%
“…29 The elevation of potassium due to hemolysis has been reported to be more important in capillary blood samples compared to venous blood samples, which is of special interest to POCT applications. 32 It was also shown that temperature during transport might lead to misdiagnosis and "pseudo hyperkalemia", or so-called "seasonal pseudohyperkalemia". 33 To alleviate this issue, a study showed that the introduction of centrifuges in UK GP surgeries led to a reduction of these cases, thereby proving the benefits of rapid, point-of-care plasma extraction.…”
Section: Influence Of Hemolysis In Blood Samplesmentioning
confidence: 99%
“…Of course, we considered the possibility that high LDH level might be due to difficulty experienced during collection or handling of the sample. Because the other laboratory results were all normal, and careful monitoring was taken, we could rule out the errors [15,16]. …”
Section: Discussionmentioning
confidence: 99%
“…For instance, differences in the effect of haemolysis on potassium assays have been demonstrated in venous versus capillary samples. 87 The setting of acceptability limits is of great significance in the interpretation of results of interference studies. Manufacturers often use AE10% as their criterion of acceptability for their assay performance claims with regard to interferences (Table 2).…”
Section: Interference Testingmentioning
confidence: 99%